Development of Prototype for Fetching Food to Livestock - Hashim, Izzat Danish; Muhammad Soomro, Dur (Evolution in Electrical and Electronic Engineering, 2023)
This project aimed to develop a prototype for fetching food to livestock by using the IoT to control a servo motor as a food dispenser and a DC motor as a conveyor for serving food to livestock. The objective was to improve the efficiency and accuracy of feeding the food to livestock, reduce the time to feed food and enhance the overall health and productivity of the livestock. The system was integrated with sensors and a microcontroller to monitor food consumption and adjust the dispensing rate accordingly. A prototype was designed and tested. A prototype for fetching food systems to livestock has been developing on a small scale. This research highlights the potential of using servo motors and DC motors in feeding systems as a way to improve the feeding of food to livestock and increase their productivity.